Pola Penggunaan Antimalaria pada Pasien Malaria di Instalasi Rawat Inap RSUD Jayapura Periode Januari–Desember 2020: Pattern of Antimalarial Drug in Malaria Patients in the Jayapura Hospital Inpatient Installation During January – Desember 2020 - Kornelius Yustico Trimedya Purba; Vita Olivia Siregar; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
The Jayapura city is one of the endemic areas of malaria in the province of Papua. The use of antimalarial medicine in hospitals has adjusted to a pattern of successful therapy in previous years. The study aims to know the pattern of antimalarial use in malarial patients at the jayapura hospital installation in January - December 2020. The method of research used is a non-experimental study with a descriptive design from the retrospective data that sources the data of the treatment records of malaria patients. Studies show that the age of 17-25 became the most common age to develop malaria by 38 patients (38%). The male group became dominant compared with the female population of 60 (60%). Students are the primary target of malaria with 38 patients (38%). Tropical malaria is the most common of 62 patients (62%). Combination of primaquine + artesunate therapy reaches (66%). For precise indications and precise intervals of time entering into the precision of the treatment of malaria with accuracy (100%) while for right the medicine has a percentage (92%) and the right dosage has a percentage (99%) so it can be maximized in the future.